INCLUSIVE AND SUSTAINABLE EDUCATION FOR STUDENTS WITH COGNITIVE DISABILITIES - Yadira Higuera Jaimes; Nancy Andrea Romero Turizo (LÍNEA IMAGINARIA, 2025)
This article offers a critical reflection on inclusive and sustainable education for students with cognitive disabilities within school contexts. It begins by recognizing a dual crisis—environmental and educational—that, despite scientific and technological advances, has not translated into transformative pedagogical practices. A traditional, memorization-centered model continues to dominate, often excluding students who most need comprehensive approaches. To address this issue, a bibliographic review was conducted, aiming to understand how education can respond to current challenges through inclusive, equitable, and sustainable frameworks. Key themes include the curricular integration of cognitive diversity, the ethical responsibility of teachers in the face of exclusion, and the need to foster critically engaged citizens in a complex world. The findings highlight the urgency of reshaping schools as spaces that uphold respect, justice, and active participation, recognizing education as a universal human right. Inclusion means more than access; it demands quality, dignity, and ethical commitment. Ultimately, sowing seeds of change involves preparing students for life through human values, ecological awareness, and social transformation.